Water and nutrient uptake in Vriesea cultivars: Trichomes vs. Roots - Vanhoutte, B.; Schenkels, L.; Ceusters, J.; De Proft, M. P.
Vriesea species are tank-type Bromeliaceae, mainly occurring as epiphytes. With their absorbing trichomes and their leaves arranged into water and nutrient catching tanks, they are able to thrive in tree canopies where water and nutrient uptake by the roots is limited. However, when commercially cultivated in greenhouses as ornamentals these plants grow in a very different environment: they are offered ample water and nutrients, and their roots develop in horticultural substrates. This study shows that under commercial cultivation conditions, Vriesea cultivars take up water and nutrients both by their roots and their leaf trichomes. As plants develop throughout the production cycle the relative share of water and nutrient uptake by the roots diminishes in all cultivars tested, but to a different extent. These cultivar-specific differences in water and nutrient uptake can be attributed to differences in tank form, trichome uptake kinetics, trichome densities and ultimately to genetic background.
Keywords: VRIESEA; TRICHOMES; WATER UPTAKE; NUTRIENT UPTAKE; BROMELIACEAE